Strategy for The Development of Sustainable Integrated Tourism Areas in Sedati District Sidoarjo - Muchlisiniyati Safeyah; Wiwik Dwi Susanti; Fairuz Mutia (Sinektika: Jurnal Arsitektur, 2022)
The tourism village trend that is developing at this time is one of the important parameters in the development of Sedati District. Sedati District has some potential to be developed into a tourist village. The potential of tourist villages in Sedati District can be grouped into three types of tourist villages, namely coastal, arts and culture, and history. However, the diversity of tourism potential that is owned is not widely known by the wider community, has not been managed properly, and has not been integrated between one tourist village and another. The purpose of this study is to explore the potential and constraints of tourist villages in Sedati District so that strategies can be drawn up for the development of a sustainable integrated tourism area. The research is qualitative and quantitative, with a research approach using the positivism paradigm. The data analysis technique in this study used descriptive qualitative analysis and SWOT analysis. Sedati District has 8 villages that have the potential to be developed as integrated tourism villages. Have something to do, something to see, and something to buy. The weakness is that tourism objects are not visually attractive, do not involve the community, lack promotion, and there is no branding. The development strategy that can be carried out is to integrate and collaborate with the three existing types of tourism; create a regional arrangement design concept and visual quality according to the characteristics; integrate land conversion according to the RTRW; educate and prepare the community and village officials as tourism actors; synergize inter-village policies at the sub-district level; establish cooperation with the Navy, and the private sector; promote and strengthen branding with internet media; forming pokdarwis to realize the development of tourist villages